Design Dryblock In Digital Thermometer Calibrator Based on Arduino - Ardelina Ramadhani; Endang Dian Setioningsih; syaifuddin syaifuddin (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2020)
Abstrak- Dryblock is a versatile temperature calibrator that works with heating. Most of the dry block using one or more inserts that can be exchanged where the holes are drilled. These holes accommodate various temperature sensors to be calibrated. diameter hole size in accordance with the temperature sensor into tested.The device is very simple way, namely by inserting a thermometer to be calibrated into a hole that has been provided on the tool and will be compared with LM35 temperature readings that already appears on the LCD screen so that it will look at the difference between the thermometer display.This temperature reading and temperature modules have been compared with a calibrated thermometer in BPFK Surabaya, and the biggest mistake in getting the smallest is 0, 2% and 0.1%